In Part 1 Stage Active Phase with Severe Preeclampsia: Case Study - Ritonga, Siti Nurcahyani; Sintya, Revina (Nursing Case Insight Journal, 2024)
Preeclampsia is an ongoing complication of pregnancy. Regular antenatal care (ANC) is expected to prevent the development of preeclampsia or enable its earlier detection, thereby reducing subsequent danger. The impact of hypertension in pregnancy is: Preeclampsia and eclampsia can occur and can have an impact on the mother and fetus. This case study aims to analyze midwifery care for preeclampsia patients. The author uses a descriptive analytical method in the form of a case study approach in midwifery care for patients which includes review of subjective, objective data, analysis, management and documentation in Subjective, Objective, Analysis, Planning (SOAP) form. Based on the data review, it was found that signs and symptoms of severe preeclampsia were present complaints of dizziness, anxiety, heartburn and a history of high hypertension starting at 28 weeks of gestation. Inspection Vital signs BP 160/110 mmHg, physical examination shows edema in the lower extremities, and supporting examinations showed urine protein +1. Management has been carried out according to midwifery care in women giving birth with severe preeclampsia, namely RL 500 cc + 6 infusion grams of MgSO4 40% maintenance dose 20 drops/minute, Nifedipine 1 x 10 mg, Methyldopamet 2 x 20 mg administered.